Preparation of polymer hollow microsphere filled epoxy resin-based syntactic foam material and its performance analysis - Xue, Wei; Feng, Yi; Wang, Jian; Fang, Zumin; Shen, Jiawen; Ma, Yunfan; Wang, Yueru; Liu, Hechen; Li, Le (Frontiers in Materials, 2024)
To explore sound-absorbing and flame-retardant materials that meet the requirements for double-shielded and double-insulated Faraday cages, polymethyl methacrylate (PMMA) microspheres were incorporated into epoxy resin-based syntactic foam materials for testing and analysis. The addition of PMMA microspheres was found to enhance the electrical, mechanical, sound-absorbing, and flame-retardant properties of the syntactic foam, providing a potential reference for applications in high-voltage hall shielding and sound absorption. Syntactic foams with four concentrations of PMMA microspheres (0%, 0.5%, 1%, and 2%) were prepared. High-voltage breakdown testing, impedance tube testing for sound absorption coefficient, cone calorimetry for flame-retardant performance, and tensile and bending tests were conducted. Results showed that as the concentration of PMMA microspheres increased, improvements were observed in the tensile, bending, flame-retardant, and sound absorption properties of the syntactic foams, while breakdown strength decreased. These findings provide valuable insights into the application of syntactic foam materials in double-insulation, double-shielded Faraday cages.